Architecture, symbolic capital and elite mobilisations: The case of the Royal Bank of Scotland corporate campus. (September 2016) - Kerr, Ron; Robinson, Sarah
In this article, we apply the conceptual framework of Pierre Bourdieu, in particular forms of capital, social fields, field of power and modes of domination, to demonstrate how the study of a symbolically powerful building can provide insights into what are often opaque elite interactions. In order to do this, we focus on the corporate campus headquarters of a powerful financial institution, the Royal Bank of Scotland in the context of Scotland in the period 2000–2009. We pose the following questions: What is the relationship between corporate space and the field of power? What role does a corporate building play in circuits of capital conversion? What does this case tell us about the role of architecture in elite mobilisations? In addressing these questions, we contribute to critical organisation studies by identifying and theorising the role of corporate space in inter-elite dynamics and circuits of capital conversion. This approach, we argue, provides a methodological lever which could be applied to other symbolically important buildings in order to understand the nature and role of inter-field interactions in the conception and realisation of such buildings.